Heat Monitor 2020 and 2021: Heating energy consumption down slightly but climate targets still not met - Till Köveker; Mats Kröger; Franziska Schütze (DIW Weekly Report, 2022)
The building sector plays a major role when it comes to meeting climate targets. An analysis by DIW Berlin based on data from energy provider ista SE shows that in the past two years both the temperature-adjusted heat consumption in German multi-apartment buildings and the temperature-adjusted CO2 emissions have dropped slightly. As positive as this decrease is-despite the increase in homeworking due to the coronavirus pandemic-it is nowhere near enough to meet the climate targets. For this to happen, it would be necessary to achieve annual CO2 emission reductions in the order of magnitude of around four percent of emissions in 2020. The soaring heat energy prices resulting from the war in Ukraine may cause a noticeable decrease in energy consumption and CO2 emissions because households will heat less for financial reasons. The government will need to go beyond delivering short-term relief packages and use the momentum for long term measures, making buildings more energy efficient. For energy saving and climate protection reasons, the government needs to accelerate investment in energy-efficient building renovations and in the use of renewable energies in the heating sector.
Keywords: R31; Q21; Q40; 330; Heating demand; heating costs; building energy efficiency; residential buildings; gas prices